Single-Cell Transcriptomics in Cancer Immunobiology: The Future of Precision Oncology - Valdes-Mora, Fatima; Handler, Kristina; Law, Andrew M. K.; Salomon, Robert; Oakes, Samantha R.; Ormandy, Christopher J.; Gallego-Ortega, David (Frontiers in Immunology, 2018)
Cancer is a heterogeneous and complex disease. Tumours are formed by cancer cells and a myriad of non-cancerous cell types that together with the extracellular matrix form the tumour microenvironment. These cancer-associated cells and components contribute to shape the progression of cancer and are deeply involved in patient outcome. The immune system is an essential part of the tumour microenvironment, and induction of cancer immunotolerance is a necessary step involved in tumour formation and growth. Immune mechanisms are intimately associated with cancer progression, invasion, and metastasis; as well as to tumour dormancy and modulation of sensitivity to drug therapy. Transcriptome analyses have been extensively used to understand the heterogeneity of tumours, classifying tumours into molecular subtypes and establishing signatures that predict response to therapy and patient outcomes. However, the classification of the tumour cell diversity and specially the identification of rare populations has been limited in these transcriptomic analyses of bulk tumour cell populations. Massively-parallel single-cell RNAseq analysis has emerged as a powerful method to unravel heterogeneity and to study rare cell populations in cancer, through unsupervised sampling and modelling of transcriptional states in single cells. In this context, the study of the role of the immune system in cancer would benefit from single cell approaches, as it will enable the characterisation and/or discovery of the cell types and pathways involved in cancer immunotolerance otherwise missed in bulk transcriptomic information. Thus, the analysis of gene expression patterns at single cell resolution holds the potential to provide key information to develop precise and personalized cancer treatment including immunotherapy. This review is focused on the latest single-cell RNAseq methodologies able to agnostically study thousands of tumour cells as well as targeted single-cell RNAseq to study rare populations within tumours. In particular, we will discuss methods to study the immune system in cancer. We will also discuss the current challenges to the study of cancer at the single cell level and the potential solutions to the current approaches.